Saturation effect of brachial-ankle pulse wave velocity on first stroke in adults with hypertension: a prospective cohort study - Zhou, Wei; Zhu, Lingjuan; Wang, Tao; Yu, Chao; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPrevious studies have reported a linear association between brachial-ankle pulse wave velocity (baPWV) and stroke in hypertensive individuals, primarily in foreign countries, with few studies conducted in China. This study aimed to investigate the saturation effect of baPWV on the first stroke in adults with hypertension and propose a possible inflection point of baPWV at which the saturation effect occurs.MethodsA total of 7,198 adults with hypertension and baseline baPWV were enrolled from the China Hypertension Registry Study. The outcome of this study was the first stroke. Cox proportional hazards regression, smoothing curve fitting (restricted cubic spline), Kaplan–Meier survival curve analysis, and subgroup analysis were used to investigate the association between baPWV and first stroke.ResultsA total of 281 patients experienced their first stroke during an average of four years of follow-up. There was a saturation effect of baPWV with an inflection value of 17.5 m/s on the first stroke. For baPWV < 17.5 m/s, each 1 m/s increment was associated with a 31% higher risk of first stroke (hazard ratio [HR]: 1.31, 95% confidence interval [CI]: 1.17, 1.47). For baPWV ≥ 17.5 m/s, there was no significant association between baPWV and first stroke (HR: 0.99, 95% CI: 0.96, 1.02) (for log-likelihood ratio test P < 0.001). Kaplan–Meier curves revealed a continual increase in the cumulative hazard for the first stroke from quartile 1–3 levels of baPWV (log-rank P < 0.001), whereas a non-significant difference in cumulative hazard between quartiles 3 and 4 was observed (log-rank P = 0.873).ConclusionBaPWV exhibited a saturation effect on the first stroke in hypertensive adults in China. Increased baPWV was positively associated with a higher risk of first stroke among hypertensive adults with a baPWV < 17.5 m/s.